Climate Change Management : Special Topics in the Context of Asia. - Huong Ha, Thi Thu (Business Expert Press, 2018)
This book includes seven chapters focusing on special issues of climate change management in Asia. The first chapter discusses the challenges with regard to climate change governance. The second chapter examines the impact of climate change on agriculture and food security in Nepal from socio-economic perspectives. The findings reveal that climate change entails much adverse effect, for example, contributing to loss of species and local landraces, reducing agricultural productivity and yield, and contributing to the emerged labor crisis in the rural areas. The third chapter is a rare work which explores a new dimension of climate change management, that is, environmental knowledge management. The fourth chapter also touches on a special topic regarding climate change, that is, legal issues in the maritime sector. This chapter reviews the climate change challenges faced by the maritime industry, and the current legal framework governing the maritime sector in South Asia with regard to climate change. The fifth chapter examines how the legal industry in Malaysia responds to climate change to contribute to resolving such global issues, and to the development of the country's economic growth. The sixth chapter, about the agriculture sector in Japan, investigates whether the adaptive method of introducing high-temperature tolerant varieties and the mitigation strategy of reducing chemical inputs affect the product price of rice in Japan. Finally, the last chapter proposes that robust strategies and policies from the relevant authorities are required to provide directions to stakeholders so that they can effectively and efficiently respond to climate change challenges.